Entre consciências vigiadas e identidades híbridas : a trajetória de Antônio Henriques e os percursos culturais e identitários dos cristãos-novos face à atuação da inquisição portuguesa no âmbito da diáspora atlântica sefardita (1603- 1662) - Santos, Nelson Santana (2019)
During the Dutch dominion over northeastern Brazil (1630-1654) the practice of Judaism was officially permitted, unlike in the rest of the Colonial Period. After the Portuguese reconquest, the Jewish religion was again banned and its adherents, resident there, were granted a period of three months to leave the region. Most of the Jews went to other countries, especially to Holland itself. To the few that stayed remained the compulsory practice of Christianity and the risk of being arrested and prosecuted by the Inquisition. The present dissertation seeks to investigate the possible identity conflicts experienced by the New Christian prisoners (and prosecuted) by the Portuguese Inquisition, residing in the Captaincy of Pernambuco, in this period immediately after the end of the Dutch rule. It seeks to verify whether the circumstance of such New Christians situated in a context of transition from an environment of religious freedom of conscience to a scenario of retaking the obligation of Catholicism and inquisitorial vigilance has generated identity conflicts and, if so, what the characteristics of these conflicts, as well as any strategies adopted to overcome them. To that purpose, it was decided to study the trajectory of Antônio Henriques, moreover, Isaac Cohen Henriques, the only New Christian imprisoned by the Portuguese Inquisition in the post-Dutch period for the public practice of Judaism during the Dutch dominion over Brazil. The importance of the study of its trajectory is due to the fact that it is the only case (sufficiently documented) of a New Christian who lived the double experience of the public exercise of Judaism and the subsequent decision to remain in Brazil after the departure of the Dutch, even at the risk of being arrested and convicted by the Inquisition.